Comprehensive analysis of tubular combustion chambers in Turbo-Ramjet engines for enhanced hypersonic propulsion - Nikhil S Prakash; Akhil G; Amjith L R (FirePhysChem)
Anticipating a doubling in global air travel demand by 2040, the present work underscores the need for innovation in aviation propulsion systems. This study presents the design and analysis of tubular combustors for lower Mach numbers in Turbo-Ramjet engines, utilizing input parameters derived from automotive turbochargers. The combustion chamber design is based on thermodynamic analysis, incorporating empirical data for optimal configuration. Three-dimensional simulations were conducted using CATIA V5 and ANSYS 2018 software to model and analyze three geometric configurations of chamber. Various configurations, including those with and without cooling holes and swirl vanes, were used to analyze fluid dynamics and combustion behavior. Velocity and temperature profiles were assessed at specific positions along the combustor, notably at x = 73 mm, x = 138 mm, and x = 195 mm. Simulation results indicate that MODEL 1, without cooling holes, exhibited non-uniform combustion with a peak surface temperature. MODEL 2 showed poor flame stabilization due to the absence of a swirl vane. MODEL 3, achieved optimal performance, with a peak temperature of 2241 K and outlet temperature reduction near the walls to approximately 1124 K and with shortest ignition delay of 40 mm. These findings, supported by graphical results, highlight MODEL 3′s suitability for efficient combustor design and performance optimization.